Exploring Deixis in Taylor Swift's Song 'Cardigan': A Descriptive Qualitative Analysis - S, Kartika (LinguaEducare: Journal of English and Linguistic Studies, 2024)
This study explores the use of deixis—a pragmatic linguistic concept of context-dependent expressions—in Taylor Swift's song "Cardigan." Utilizing a descriptive qualitative research design, the analysis categorizes deictic expressions in the lyrics into five types: personal, spatial, temporal, social, and discourse deixis. Personal deixis, represented by pronouns like "I," "you," and "we," establishes a sense of intimacy and emotional engagement by drawing listeners into the narrative. Spatial deixis, such as "back when you could touch me," evokes vivid imagery that enhances the song's nostalgic and intimate feel. Temporal deixis anchors the narrative in time, emphasizing themes of growth, reflection, and the lasting impact of past experiences, as seen in phrases like "when you are young." Social deixis reflects the complexities of relational dynamics, while discourse deixis helps maintain narrative cohesion by connecting different parts of the song. The findings highlight deixis as a powerful tool in songwriting, enabling artists to create emotionally compelling and relatable lyrics. This research underscores the importance of deixis in enhancing lyrical storytelling and emotional impact in music, offering insights for songwriters and language educators. However, the study's focus on a single song limits its generalizability across genres and languages. Future research should explore a wider range of songs and cultural contexts to gain a more comprehensive understanding of deixis in music. Comparative studies across languages and genres could further illuminate the universality and variability of this linguistic phenomenon in artistic expressions.